Structural and Electrical Properties of Li–Ni Nanoferrites Synthesised by Citrate Gel Autocombustion Method. (20th October 2014) - Aravind, G.; Ravinder, D.; Nathanial, V.
Abstract : An attempt has been made to synthesize nanocrystalline lithium-nickel ferrites with a compositional formula Li0.5−0.5 x Ni x Fe2.5−0.5 x O4 (wherex = 0.0 to 1.0 with step of 0.2) by a low temperature citrate gel autocombustion method. Single phase cubic structure is confirmed by X-ray diffraction analysis. This result demonstrates that the prepared samples are homogeneous and the sharp peaks reveal that the samples are in good crystalline form. As the Ni concentration is increased, various interesting changes in the values of the structural parameters like lattice parameter, X-ray density, bulk density, and porosity have been observed. The surface morphology of the prepared samples was studied using scanning electron microscopy (SEM). The DC resistivity measurements were carried out using two-probe method from 200°C to 600°C. The variation oflog ⁡ ( σ T ) with reciprocal of temperature shows a discontinuity at Curie temperature.log ⁡ ( σ T ) versus1 / T plot of the pure lithium ferrites is almost linear which indicates the Curie temperature of the pure lithium ferrites was beyond our measured temperature. The dielectric properties of these ferrites have been studied using a LCR meter from the room temperature to 700 K at various frequencies up to 5 MHz, which reveals that all the prepared samples have dielectric transition temperature around 600 K.